A 3‐D thermal regime model suitable for cold accumulation zones of polythermal mountain glaciers. Issue 9 (19th September 2014) - Gilbert, A.; Gagliardini, O.; Vincent, C.; Wagnon, P.
Abstract Analysis of the thermal and mechanical response of high altitude glaciers to climate change is crucial to assess future glacier hazards associated with thermal regime changes. This paper presents a new fully thermo‐mechanically coupled transient thermal regime model including enthalpy transport, firn densification, full‐Stokes porous flow, free surface evolution, strain heating, surface meltwater percolation, and refreezing. The model is forced by daily air temperature data and can therefore be used to perform prognostic simulations for different future climate scenarios. The set of equations is solved using the finite element ice sheet/ice flow model Elmer/Ice. This model is applied to the Col du Dôme glacier (Mont Blanc area, 4250 m a.s.l., France) where a comprehensive data set is available. The results show that the model is capable of reproducing observed density and velocity fields as well as borehole temperature evolution. The strong spatial variability of englacial temperature change observed at Col du Dôme is well reproduced. This spatial variability is mainly a result of the variability of the slope aspect of the glacier surface and snow accumulation. Results support the use of this model to study the influence of climate change on cold accumulation zones, in particular to estimate where and under what conditions glaciers will become temperate in the future.